ANALISIS PEMBUATAN DAN POTENSI EKOENZIM KULIT BUAH JERUK NIPIS (Citrus aurantiifolia) SEBAGAI UPAYA PENINGKATAN KESEHATAN MANDIRI RUMAH TANGGA - Hupitoyo, Hupitoyo; Hariyanto, Tanto; Kurniawati, Atik (Media Penelitian dan Pengembangan Kesehatan, 2024)
Lime peel ecoenzyme (Citrus aurantifolia) is a microbial-based product made by fermenting the fruit peel for more than one month. The study aimed to analyze the ecoenzyme product from lime peel (C. aurantifolia) and its potential as an antiseptic so that it becomes one of the independent health improvement efforts on a household scale. The research design was laboratory experiments. The data described descriptively based on the results obtained from laboratory experiments. The research results showed that ecoenzyme contains a complex of organic ingredients as a natural antiseptic that can be used in the household such as 19 types of organic acids, 17 types of flavonoids, 16 types of carbohydrates and 19 types of amino acids which have potential as antiseptics. The study concluded that the ecoenzyme product from lime peel (C. aurantifolia) has potential as an antiseptic because it contains a complex of organic ingredients as a natural antiseptic that can be used in the household. Potential antiseptics can be in the form of dish cleaners, fruit and vegetable washes. Instead of being an antiseptic, ecoenzyme liquid can be used as a plant fertilizer and compost activator which can be applied to reduce household waste.